Dyslipidemia in coronavirus disease 2019 pneumonia patients - Peng Cao; Sanlan Wu; Tingting Wu; Qilin Zhang; Rui Zhang; Yu Zhang (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2020)
Coronavirus disease 2019 (COVID-19) pandemic has become a global threat to public health, risk factors of COVID-19 is in urgent need in this fight. We collected data and clinical records from 123 COVID-19 patients at Wuhan Union hospital, China. Of 123 patients enrolled, 6 died in hospital and the other 117 survived. It is noteworthy that lipid levels, especially HDL-c, significantly differed between survivors and non-survivors. We suppose that HDL-c might also be a risk factor of COVID-19. Medical staff should pay more attention to the lipid levels of COVID-19 infected patients.